Performa sistem autocascade dengan menggunakan karbondioksida sebagai refrigeran campuran - Nasruddin Nasruddin; Ardi Yuliono; Darwin Rio Budi Syaka (Jurnal Rekayasa Proses, 2011)
Most refrigeration systems today use refrigerant which causes ozone depletion or global warming. Therefore, alternative natural refrigerants are highly required. One potential candidate is CO2. However, high pressure of CO2 limits its application in conventional refrigeration system. To solve this problem, a low investment cost of autocascade refrigeration system is used. This research investigated autocascade refrigeration system using a mixture of CO2 (R744) and R12, in comparison with environmentally friendly refrigerant mixture of CO2 (R744) and R600a. The parameters analyzed were (1) evaporation temperature, (2) condensation temperature, (3) suction temperature, (4) discharge temperature, (5) suction pressure, and (5) discharge pressure. The experiment results showed that an increase of CO2 concentration by 10% or more in the autocascade refrigeration system could raise system pressure. Therefore, the increase of CO2 pressure should be within the allowable limit of the working pressure of the compressor.